Determination of the Poisson's ratio of viscoelastic materials based on the linear rheological model using instrumented indentation. Issue 1 (2nd January 2016) - Liu, Erqiang; Xiao, Gesheng; Wang, Hefeng; Yang, Xuexia; Shu, Xuefeng
ABSTRACT: Based on the linear rheological constitutive model that is used to describe viscoelastic-plastic behavior of viscoelastic materials, a formula of the Poisson's ratio was deduced according to the relationship between the shear creep compliance and tensile compliance. Instrumented indentation under various loading conditions and universal creep tests were performed on polyamide 12 samples to obtain the relevant rheological parameters. Results show that the Poisson's ratio for a step load indentation can obtain a constant but overrated value. However, the Poisson's ratio approaches an asymptotic value and an accurate value can be gained at a certain loading rate.